Mapping of two loci affecting the synthesis and structure of a periplasmic protein involved in arginine and ornithine transport in Escherichia coli K-12. - Celis, R T (1982)
The map location of two genes, abpR and abpS, was established. The abpR locus is responsible for the synthesis and the abpS locus is responsible for the structure of the arginine-ornithine-binding protein, a required component of the arginine-ornithine transport system of Escherichia coli. Two loci that result in elevated synthesis of the arginine-ornithine-binding protein and in an altered protein were mapped by bacterial conjugation and transduction studies. The mapping showed that the two genes lie in close proximity near the argA genetic marker in the order, with respect to argA, of argA abpR abpS. The maximal influx of arginine into an abpR mutant, which produces the arginine-ornithine-binding protein in an elevated amount, was substantially higher than the value obtained with an isogenic wild-type strain (apbR+). It also was observed that there was a close similarity between the affinity of the transport system for its substrate and the in vitro affinity of the binding protein for arginine both in the case of the isogenic wild type (abpS+) and a mutant (abpS6) carrying an altered protein. These results were consistent with the concept that the binding protein modulates the affinity of the transport system and suggest that it is the step of substrate recognition by the periplasmic protein which is rate-limiting in the entire process of transport at maximal influx.